KONSEP MUDHARABAH DAN MUSYARAKAH DALAM PERBANKAN SYARIAH MENURUT ABDULLAH SAEED - Segara, Edo (Mutanaqishah : Journal of Islamic Banking, 2021)
This article discusses the concept of profit sharing which is an issue in the debate of Islamic Banking in Indonesia. Researchers try to review how the concept of profit sharing is elaborated with Abdullah Saeed's thoughts. Abdullah Saeed is an Australian scholar and scholar studying Islamic studies. He is currently the Omani Professor of Arabic and Islamic Studies at the University of Melbourne. He is known for his progressive views on religious freedom in Islam.